1988
DOI: 10.1093/ageing/17.3.164
|View full text |Cite
|
Sign up to set email alerts
|

Blood Glucose and Prognosis of Acute Stroke

Abstract: To study the relation of blood glucose soon after the onset of stroke and outcome in terms of fatality and functional recovery 6 months later, two prospective studies were performed. Fasting blood glucose measured within 48 hours of onset was significantly higher in those who died than in those who survived. However, random blood glucose, mean daily blood glucose and HbA1 were not related to fatality or functional recovery. Fasting blood glucose levels soon after the stroke were significantly higher than those… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…11 The use of a random versus fasting blood sugar concentration also appears to influence the results. 12 We found a clear difference in the fasting glucose levels between the good and poor outcome groups that persisted for up to 1 month, confirming the findings of Pulsinelli et al 1 and others. 2 The large proportion of our patients who had either died or were severely disabled at 6 months is consistent with the known consequences of stroke in an elderly population.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…11 The use of a random versus fasting blood sugar concentration also appears to influence the results. 12 We found a clear difference in the fasting glucose levels between the good and poor outcome groups that persisted for up to 1 month, confirming the findings of Pulsinelli et al 1 and others. 2 The large proportion of our patients who had either died or were severely disabled at 6 months is consistent with the known consequences of stroke in an elderly population.…”
Section: Discussionsupporting
confidence: 91%
“…It might be due to the unmasking of a premorbid abnormal glucose tolerance. 14 - 15 Power et al 12 argued, however, that the relation between outcome and the fasting, rather than the random, blood sugar concentration pointed toward the hyperglycemia being a function of a stress response and not of preexisting glucose intolerance. In a large study, Woo et al 16 found a greater relation between outcome and stress hyperglycemia in nondiabetics than in known or newly diagnosed diabetics.…”
Section: Discussionmentioning
confidence: 99%
“…21 Thirty-one articles describing 32 cohort studies (1 article described 2 separate cohorts 22 ) therefore were included in the overview. 1,[7][8][9][10][11][12] …”
Section: Selection Of Studiesmentioning
confidence: 99%
“…The assessment was based on a validated scale (Barthel Index, 10,23,45 Glasgow Outcome Scale, 37,45 Canadian Stroke Scale, 24 and Canadian Neurological Scale 25 ) in 6 of these studies. The remainder used the following qualitative descriptions of poor functional recovery: unable to return to any form of work, 7 persistent disability, 26 need for residential placement, 27 dependent in activities of daily living, 11,22,28 and stable deficit with no recovery. 29 Diabetes status was assigned on the basis of a history of diabetes or treatment with hypoglycemic agents in 20 of 32 studies ‡; in 8 studies, an elevated glycosylated hemoglobin 8,12,23,32,35,37 or persistent or marked hyperglycemia 10,25 was used to define diabetes.…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation